Unraveling fine-scale genetic structure in endangered hawksbill turtle (Eretmochelys imbricata) in Indonesia: implications for management strategies - Sani, Lalu M. Iqbal; Jamaludin,; Hadiko, Gunawan; Herma, Ema; Inoguchi, Emi; Jensen, Michael P.; Madden, Christine A.; Nishizawa, Hideaki; Maryani, Leni; Farajallah, Achmad; Subhan, Beginer; Bengen, Dietriech G.; et al. (Frontiers in Marine Science, 2024)
Indonesia is an archipelagic country that provides important nesting and foraging habitats for the critically endangered hawksbill turtle (Eretmochelys imbricata). Although many studies have investigated this migratory species globally, there is a lack of information on the population structure and geographic boundary of this species in Indonesia. This study aims to investigate the genetic diversity and population structure of six nesting sites in the Java Sea region of Indonesia. The control region (d-loop) sequence (818 bp) was obtained from 152 individuals, resulting in 20 haplotypes. This study revealed 13 new haplotypes, 12 of which were rare and observed only in a single sampling location. Results showed that the Indonesian population shares haplotypes with rookeries from Peninsular Malaysia and Australia, as indicated by EiIP08 and EiIP49. The haplotype diversity (h) was highest at the more northern rookery sites (Segama Besar Island, Kimar Island, East Belitung, Penambun Island) (h: 0.6033 - 0.9167; 4 - 9 haplotypes) compared to the other two rookeries located in the Seribu Archipelago (Tidung Island and Harapan Island) (h: 0.3354 - 0.5965; 3 - 6 haplotypes). Furthermore, population structure analysis showed a pan-mixed population between Tidung Island and Harapan Island (FST: 0.003, P > 0.05) but significant population structure across all other rookery sites (FST: 0.083 - 0.486, P < 0.05), resulting in five newly identified Management Units (MUs) in this area. This study showed the presence of a complex population structure with local haplotypes and narrow population boundaries for rookeries in relatively close proximity within the Java Sea, prompting local management and highlighting the need for more research on hawksbill turtle populations in Indonesia.